Diagnóstico de pericarditis inflamatória idiopática en un perro. Reporte de un caso - Yepes M., Catalina M.; Gómez G., Leonardo F.; Orozco P., Sonia C. (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary This is a case of a nine years old male Bóxer, which presented exercise intolerance, weak cardiac sounds and abdominal distension caused by ascites. After performing ancillary tests like radiography, echocardiography and electrocardiography a severe accumulation of pericardial liquid which was generating a cardiac tamponade was confirmed. After the fluid was submitted to cytological evaluation and other possible diagnoses were excluded, it was determined the diagnosis of Inflammatory Idiopathic Pericarditis (IIP).